PENGARUH PENDEMI COVID-19 TERHADAP KINERJA PERUSAHAAN (PROFITABILITAS, LIKUIDITAS, FAKTOR EKSTERNAL, DAN HARGA SAHAM) PADA PERUSAHAAN INDUSTRI OTOMOTIF DI BEI - Hastuti Sari Sari Budiningsih; Zulkifli Zulkifli; Widarto Rachbini (LPPM Universitas Banten jaya, 2022)
This research’s purpose is to determine the impact of the COVID-19 pandemic on the performance of automotive companies listed on the Indonesia Stock Exchange. In addition, this research is also conducted for determining the effect of the external factors (inflation, interest rates), liquidity (current ratio, cash ratio), profitability (ROI, ROA, NPM) and stock prices in automotive industry companies listed on the Indonesia Stock Exchange. The method used in this research is a quantitative method and uses Structural Equation Mode analysis. The sample used in this research are 5(five) automotive industry companies listed on the Indonesia Stock Exchange. The data used is quarterly financial report data of 2019 (before the COVID-19 pandemic) and 2020 (after the COVID-19 pandemic). Based on the research of the study indicate that external factors in this case inflation and interest rates have a significant positive effect on stock prices; Liquidity has a significant positive effect on profitability; Profitability has a significant positive effect on stock prices; External factors have no significant effect on stock prices; Liquidity has a significant negative effect on stock prices. The overall financial performance of automotive industry companies listed on the IDX decreased due to the COVID-19 pandemic, before the pandemic the average company performance was quite good, but with the COVID-19 pandemic the performance of the automotive industry companies decreased. A significant decrease in the level of sales resulted in a decrease in net income.